Rancang Bangun Mesin Pengering Kulit Pohon Kina Menggunakan Kontrol Pid Berbasis Mikrokontroler - Guido Dias Kalandro; Dodi Setiabudi; Ali Rizal Chaidir (J-Innovation, 2022)
Kina in plants there are several kinds of plant parts that can be taken advantage but in this case, the author will discuss the special problems of cinchona bark between 0.5 meters and 0.5 meters from the bottom and top of the plant kina. Because the bark of cinchona was the producers took to be resold to the pharmaceutical industry. During this time many of the manufacturers of leather kina kina dry the skin by way menjemuran directly in the sun. In this process the skin needs time producers such as 5-6 days if no disruption of nature such as rain, clouds, etc.. For example, if there is rain then the drying process can take up to 2 weeks up to maximum water levels dropped to 60% - 55%. With the above problems the writer needs to design a device where the temperature can be controlled and not influenced by disruption of natural factors.